Studi Sistem Pembangkit Listrik Tenaga Mikro Hidro Di Kampung Tingkem Kecamatan Blang Jerango Gayo Lues - Said Aiyub; Yaman Yaman; Sayuti Sayuti (Jurnal Teknologi, 2021)
Gayo Lues has an operational micro-hydro power plant in Tingkem Village, Blangjerango District, which provides lighting, piping, and electricity to the residents of Tingkem Village. Among the objectives of this study were to determine and investigate the potential of the Aih Tilis river, the discharge of the carrier channel, the volume of the tranquilizer tank, the flow of water through the pipe, and the amount of electricity generated. Transport lines, troughs, and tubing are measured and calculated in this process. The discharge obtained on the carrier line is 0.5304816 m3/s, which is equal to 5.3 liters per second. There are 72.4605 cubic meters of dry trough volume and 65.556 cubic meters of wet section volume in this experiment. When the micro-hydroelectric power plant in Tingkem is operating at full capacity, it generates 79.631 kW of electricity with a turbine efficiency value of 70 percent and a generator efficiency value of 75 percent.